Effects of imidacloprid-induced hormesis on the development and reproduction of the rose-grain aphid Metopolophium dirhodum (Hemiptera: Aphididae) - Li, Xinan; Li, Yaping; Zhu, Xun; Li, Xiangrui; Cheng, Dengfa; Zhang, Yunhui (Frontiers in Physiology, 2023)
Field populations of insect pests are affected by sub-lethal doses of insecticides, leading to hormesis. Imidacloprid is a neonicotinoid insecticide widely used to control various sucking insect pests, including aphids. In this study, the effects of sub-lethal concentrations of imidacloprid on the life table traits of the rose-grain aphid Metopolophium dirhodum (Walker) were evaluated on parental and first filial generations. The results showed that sub-lethal concentrations of imidacloprid significantly reduced the fecundity, adult longevity, and reproductive period of M. dirhodum in parental generation (F0). However, the imidacloprid-induced hormetic effects on development and reproduction were detected in the F1 generation. These hormetic effects were indicated by significantly higher adult longevity, fecundity, survival rate, intrinsic and finite rates of increase, and net reproductive rate of first filial generation (F1) of M. dirhodum. Our finding indicated that the application of sub-lethal concentrations of imidacloprid inhibited parental generation (F0), but it significantly stimulated the population growth of filial generation (F1) in the M. dirhodum . The results support the inclusion of insecticides in integrated pest management programs for managing wheat aphids.